The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1007/bf02090363
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin receptor genes are expressed in gastric parietal and enterochromaffin-like cells ofMastomys natalensis

Abstract: Although gastric enterochromaffin-like (ECL) carcinoid tumors are known to develop in patients with long-standing hypergastrinemia, the expression of the gastrin receptor gene in ECL cells has not yet been demonstrated. Therefore, this study was designed to examine gastrin receptor gene expression in ECL cells. Mastomys gastric mucosal cells isolated by enzyme dispersion were separated into 10 fractions (F1-10) by centrifugal elutriation. Each fraction was examined histologically to determine whether they cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…The epithelial cells expressing GR mRNA include not only ECL cells but also parietal and chief cells, confirming earlier descriptions [1,21,37].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The epithelial cells expressing GR mRNA include not only ECL cells but also parietal and chief cells, confirming earlier descriptions [1,21,37].…”
Section: Discussionsupporting
confidence: 88%
“…In the brain, it has been reported that cholecystokinin-B (CCK-B) receptors are identical to gastrin receptors (GRs) [1,17]. CCK-B receptors predominate in the CNS [7,15], but CCK-B receptors have also been identified in smooth muscle cells of the gastrointestinal tract [20], the function of which may be regulation of motility of bowel and gallbladder [16], and CCK-B has also been shown to regulate proliferation firstly of AR42-J pancreatic carcinoma cell line in rats, and subsequently of cells of gastrointestinal tract [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CCKA-Rs exhibit a 500-to 1,000-fold higher affinity for sulfated analogs of CCK than for gastrin, whereas CCKB-Rs have approximately equal affinity for both sulfated and non-sulfated peptide analogs of CCK and gastrin (32,34,46,47). CCKB-Rs are present in parietal, ECL, and probably somatostatin cells (2,4,23,27,28,41 (2,28). Immunohistochemical studies have also demonstrated the distribution of CCKB-R in the same cell types (41).…”
mentioning
confidence: 99%
“…One possible explanation for the more frequent neuroendocrine tumors over gastric adenocarcinoma in patients with hypergastrinemia may be related to the finding that although the CCK-B receptor is present on parietal cells, it is expressed more abundantly in ECL cells of the stomach. 85,86 In addition to responding to the proliferative effects of gastrin, studies also have shown that the parietal cells respond to other trophic factors secreted by the ECL-like cells by a paracrine mechanism including secretion of Reg protein, 87 heparin-binding EGF, 88 and even histamine. 89 With more sophisticated technology using lineage tracing, researchers have confirmed the presence of CCK-B receptors on the antrum stem cells that do not respond to gastrin-17.…”
Section: -63mentioning
confidence: 99%